ПОВЫШЕНИЕ ЭЛЕКТРОМАГНИТНОЙ СОВМЕСТИМОСТИ ЧАСТОТНО-ТОКОВЫХ ПРЕОБРАЗОВАТЕЛЕЙ С НАГРУЗКОЙ - Скурятин, Ю.В.; Денисевич, Н.А. (Інститут електродинаміки НАН України, Київ, 2012)
In this paper the converter of frequency of current with the output filter and zero-overshoot response operating mode is presented. The possibility to provide electromagnetic compatibility of converter and the load is shown. References 1, figures 3.